β2-Containing Nicotinic Receptors Contribute to the Organization of Sleep and Regulate Putative Micro-Arousals in Mice - Clément Léna; Daniela Popa; Régis Grailhe; P. Escourrou; Jean‐Pierre Changeux; Joëlle Adrien (2004)
The cholinergic system is involved in arousal and in rapid eye movement sleep (REMS). To evaluate the contribution of nicotinic acetylcholine receptors (nAChRs) to these functions, we studied with polygraphic recordings the regulation of sleep in mice lacking the β2 subunit gene of the nAChRs, a major component of high-affinity nicotine binding sites in the brain. Nicotine (1-2 mg/kg, i.p.) increased wakefulness in wild-type but not knock-out animals, indicating that β2-containing nAChRs mediate the arousing properties of nicotine. Under normal conditions, the β2-/- mice displayed the same amounts of waking, non-REM sleep (NREMS) and REMS as their wild-type counterparts. However, they exhibited longer REMS episodes and a reduced fragmentation of NREMS by events characterized notably by a transient drop in EEG power and frequently associated with EMG activation, tentatively referred to as micro-arousals. Respiration monitoring showed that these events were accompanied with, but not caused by, breathing irregularities. Sleep deprivation of β2-/- mice resulted in a normal increase in REMS episode duration and NREMS δ power but yielded a reduction of the number of micro-arousals in NREMS. In contrast, in β2-/- mice, a 1 hr immobilization stress failed to produce the normal rebound in REMS in the following 12 hr and, instead, was associated with increased NREMS fragmentation and sustained corticosterone levels. Our results show that the β2-containing nAChRs contribute to the organization of sleep by regulating the transient phasic activity in NREMS, the REMS onset and duration, and the REMS-promoting effect of stress.